Automated Cytochemistry in the Prediction of Remission Following Chemotherapy of Patients with De Novo Acute Myeloblasts Leukemia. Issue 1 (31st January 2016) - Winkel, Per; Olesen, Tony; Nissen, Nis I.
Abstract : In seven patients with de novo acute myeloblasts leukemia, the concentration of large unstained cells (LUC) in peripheral blood and the ratio between this quantity and the concentration of lymphocytes (LUC/ LYMPH) were measured at short intervals during each patient's clinical course. An automated differential analyzer (the Hemalog-D) was used. Both quantities were significantly higher 12 days after the institution of daunomycin and cytosine arabinoside chemotherapy (between first and second treatment series when all patients were pancytopenic) in three of the patients who did not achieve remission (mean LUC = 59 cells µ l, mean LUC/LYMPH = 13.9), as compared with four of the patients who went into remission following two series of chemotherapy (mean LUC = 16 cells/ µ l, mean LUC/LYMPH = 3.11).